Collective action for watershed management: field experiments in Colombia and Kenya (2009)
The dilemma of collective action around water use and management involves solving both the problems of provision and appropriation. Cooperation in the provision can be affected by the rival nature of the appropriation and the asymmetries in the access. We report two field experiments conducted in Colombia and Kenya. The Irrigation Game was used to explore the provision and appropriation decisions under asymmetric or sequential appropriation, complemented with a Voluntary Contribution Mechanism experiment which looks at provision decisions under symmetric appropriation. The overall results were consistent with the patterns of previous studies: the zero contribution hypotheses is rejected whereas the most effective institution to increase cooperation was face-to-face communication, and above external regulations, although we find that communication works much more effectively in Colombia. We also find that the asymmetric appropriation did reduce cooperation, though the magnitude of the social loss and the effectiveness of alternative institutional options varied across sites.